Monitoramento da resistência do Plasmodium falciparum e P. vivax aos antimaláricos em Rondônia e busca de novos esquizonticidas sanguíneos e teciduais para controle e tratamento da doença - Anna Caroline Campos Aguiar (2014)
Human malaria is the most important parasitic disease and a major public health problem. Its control remains difficult due to the lack of an effective vaccine, difficulties in the vector control and, especially, the emergency and spread of parasites resistant to most available antimalarial drugs. The specific drug treatment is a major strategy to reduce morbidity and mortality owed to malaria. The research for new antimalarials against different parasitic stages is essential and was studied in the present work. Two chloroquine analogs (BAQ and MAQ) were evaluated ex vivo against P. vivax e P. falciparum isolates from patients diagnosed in Porto Velho, Rondônia. The isolates were sensitive to MAQ and BAQ, presenting IC50 at nanomolar dose. The ex vivo sensitivity of those isolates was tested, in parallel, against the antimalarials chloroquine (CQ), mefloquine (MQ) and artesunate (AS). Most of P. vivax isolates were sensitive to CQ (IC50 of 32nM) whereas the P. falciparum isolates exhibited low sensitivity to CQ (IC50 of 70nM); all isolates were sensitive to AS and MQ. Single Nucleotide Polymorphisms were evaluated at mdr1 and crt genes, both related with antimalarial parasite resistance. Mutations were found in pfmdr1 gene at codons 184 (100%), 1042 (100%) and 1246 (100%), 1034 (84%). For the pfcrt gene, mutations were observed at codons 72 and 76 in all P. falciparum isolates. The P. vivax isolates did not present mutations. As tissue schizonticidals, fifteen primaquine derivatives (PQTZs) were evaluated against the exoritrocitic forms (EEF) of P. berghei-ANKA in vitro. The compounds inhibited the development of sporozoites into the hepatocytes, and reduced the number and the size of EEF in vitro. Only 4m was active in vivo reducing 95% the development of EEF and increasing the malaria pre-patent period in 3 days. The PQTZs were evaluated for their ability to block the malaria transmission in avian malaria (P. gallinaceum in chickens and Aedes fluviatilis) and rodent malaria (P. berghei in mice and Anopheles stephensi) using the vertebrate host treated with the compounds. The compounds 4b, 4c, 4g, 4m and 4o inhibited 100% infection of Anopheles mosquitoes by P. berghei, like primaquine, tested in parallel. The PQTZs 4m showed the best activity against EEF in vitro and in vivo and exhibited the best blocking transmission activity. This compound has yet to be evaluated against late EEF in models using P. cynomolgi malaria and/or P. vivax, aiming to develop a new drug to treat human malaria relapses.